Trace element and organic matter mobility impacted by Fe3O4-nanoparticle surface coating within wetland soil. Issue 10 (20th August 2019) - Al-Sid-Cheikh, Maya; Pédrot, Mathieu; Dia, Aline; Davranche, Mélanie; Jeanneau, Laurent; Petitjean, Patrice; Bouhnik-Le Coz, Martine; Cormier, Marc-André; Grasset, Fabien
Abstract : Mobility of n Fe3 O4 @DMSA within natural soil is higher than uncoated n Fe3 O4 which impacts differently the mobility of TEs and NOM. Abstract : Engineered oxide nanoparticles have emerged as a highly promising tool for soil remediation. However, their behaviour under complex environmental exposure ( i.e. in natural soils) remains poorly understood and a relevant issue to complete their risk assessments. Prior to using iron oxide nanoparticles in soil remediation scenarios, it is crucial to evaluate their possible role in the release of natural organic matter (NOM) and trace elements (TEs) as a vector of trace elements (TEs) as it could contribute to the contamination of aquifers. This work presents leaching experiments demonstrating the effects of magnetite ( i.e. n Fe3 O4 ) on TE and natural organic matter (NOM) transport within an organo-mineral horizon from a natural wetland. n Fe3 O4 (∼10 nm) with two different surface compositions ( i.e. uncoated and coated with dimercapto-succinic acid (DMSA)) was used in the experiments and both forms impacted the mobility of the NOM within the organo-mineral horizon. The mobility of the coated n Fe3 O4 within the horizon was higher than the uncoated n Fe3 O4 which impacted differently the mobility of TEs and NOM. The TE mobility within the horizon increased in the presence of uncoated n Fe3 O4 with a transfer of elements into the colloidal fraction. This distinctive transfer might be explained by interactions between the surface of nanoparticles and NOM. We also suggest that some of the different behaviours observed might be due to the destabilization of the DMSA coating, highlighting the critical importance of understanding the aging processes of nanoparticles under environmental exposures to assess the risks associated with their use in environmental situations.